EFEKTIVITAS STRATEGI PEMBELA JARAN PADA MADRASAH MODEL DAN KONVENSIONAL DI BEBERAPA PROVINSI INDONESIA TIMUR - Sofyan Sofyan (Al-Qalam, 2008)
This study was conducted in madrasah (Islamic High School) at severaltowns. They are Manado, Samarinda, Ternate, Gorontalo, and Makassar.Data was collected using questioner and interview. Data was analizedusing statistic analyzing.The result of study indicates that (1) effectivity of learning strategy at thisfive model madrasah is good enough. The persentation value is among77,6% (lowest) and 80,6 (highest); (2) effectivity of learning strategy atthis five conventional madrasah is also good enough. The persentationvalue is among 71,5 (lowest) and 80,7 (highest). This indicates that learningstrategy at model madrasah is better than conventional madrasah